2016
DOI: 10.3855/jidc.8160
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence rates of transfusion-transmitted infections among blood donors in Jordan

Abstract: Introduction: Statistics on the prevalence of donor screening for hepatitis B surface antigen (HBsAg) and anti-hepatitis C virus (anti-HCV) in Jordan are outdated. There are no studies on the prevalence of anti-HIV I/II, anti-human T-cell lymphotropic virus type I and II (anti-HTLV-I/II), or anti-syphilis. Data are also lacking on the prevalence and significance of using anti-HBc screening in Jordan. This study aimed to evaluate the prevalence of transfusion-transmissible infections (TTI) among donors at King … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
9
1
Order By: Relevance
“…Screening of donated blood products for infectious diseases such as hepatitis is crucial to prevent the transmission of diseases. In our previously published study on the seropositivity rates of HBsAg, anti-HBcore, and anti-HCV among healthy Blood Bank donors at King Hussein Cancer Center (KHCC), between the years 2009–2013, we found that these rates were lower in these donors relative to published data in neighboring countries [ 1 , 2 ]. Moreover, none of these donors in our previous study tested positive for anti-HIV I/II, anti-HTLV I/II, or anti-TP [ 2 ].…”
Section: Introductioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Screening of donated blood products for infectious diseases such as hepatitis is crucial to prevent the transmission of diseases. In our previously published study on the seropositivity rates of HBsAg, anti-HBcore, and anti-HCV among healthy Blood Bank donors at King Hussein Cancer Center (KHCC), between the years 2009–2013, we found that these rates were lower in these donors relative to published data in neighboring countries [ 1 , 2 ]. Moreover, none of these donors in our previous study tested positive for anti-HIV I/II, anti-HTLV I/II, or anti-TP [ 2 ].…”
Section: Introductioncontrasting
confidence: 55%
“…All blood and platelet donors were either volunteers or family replacement Jordanian citizens and were interviewed according to standard international blood donor rules and regulations. Blood bank donor-samples were processed as in our previous published work [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall seroprevalence rates of HBV, HCV, and HIV were 0.15, 0.1, and 0.004%, respectively. Similarly, low rates of TTI have been reported among blood donors from Jordan [29]. Data from Egypt in 2013 indicate that the prevalence of HIV and syphilis were extremely low [0%] but HCV and HBV were 7.2% and 2.3%, respectively, still posed a significant risk of blood transmission [30].…”
Section: Middle Eastmentioning
confidence: 99%